A rare cause of ascites in a renal transplant recipient. (18th September 2018) - Kasinadhuni, Ganesh; Sethi, Jasmine; Krishnappa, Darshan; Sharma, Yash Paul
Abstract : Thirty-five-year-old man, underwent renal transplantation 4 years back and was doing well. He now presented with complaints of ascites with engorged neck veins and dyspnoea on exertion for last 6 months. Examination showed elevated jugular venous pressure with two prominent descents, high pitched diastolic heart sound (pericardial knock). Echocardiography showed characteristic features of thickened pericardium, septal bounce, expiratory flow reversal in hepatic veins and phasic variation of mitral inflow, suggestive of constrictive pericarditis. The patient was started on empirical antitubercular therapy and diuretics. The patient symptomatically improved, but in view of persisting constrictive physiology he was planned for pericardiectomy.